Naphthoquinones: A continuing source for discovery of therapeutic antineoplastic agents. (28th November 2017) - Qiu, Han‐Yue; Wang, Peng‐Fei; Lin, Hong‐Yan; Tang, Cheng‐Yi; Zhu, Hai‐Liang; Yang, Yong‐Hua
Abstract : Naturally occurring naphthoquinones, usually in forms of botanical extracts, have been implicated with human life since ancient time, far earlier than their isolation and identification in modern era. The long use history of naphthoquinones has witnessed their functional shift from the original purposes as dyes and ornaments toward medicinal benefits. Hitherto, numerous studies have been carried out to elucidate the pharmacological profile of both natural and artificial naphthoquinones. A number of entities have been identified with promising therapeutic potential. Apart from the traditional effects of wound healing, anti‐inflammatory, hemostatic, antifertility, insecticidal and antimicrobial, etc ., the anticancer potential of naphthoquinones either in combination with other treatment approaches or on their own is being more and more realized. The molecular mechanisms of naphthoquinones in cells mainly fall into two categories as inducing oxidant stress by ROS (reactive oxygen species) generation and directly interacting with traditional therapeutic targets in a non‐oxidant mechanism. Based on this knowledge, optimized agents with naphthoquinones scaffold have been acquired and further tested. Hereby, we summarize the explored biological mechanisms of naphthoquinones in cells and review the application perspective of promising naphthoquinones in cancer therapies. Abstract : The explored biological mechanisms of naphthoquinones in cellular and the application perspective of promising naphthoquinones in cancer therapies were reviewed.